Preservation of Ejaculatory Function After Postchemotherapy Retroperitoneal Lymph Node Dissection (PC-RPLND) in Patients With Testicular Cancer: Template vs. Bilateral Resection - Hiester, Andreas; Nini, Alessandro; Fingerhut, Anna; große Siemer, Robert; Winter, Christian; Albers, Peter; Lusch, Achim (Frontiers in Surgery, 2019)
Background: Post-chemotherapy retroperitoneal lymph node dissection (PC-RPLND) plays a crucial role in treatment of metastatic non-seminomatous germ cell cancer. Objective: To evaluate the functional outcome regarding the preservation of ejaculatory function comparing a bilateral vs. unilateral template resection in PC-RPLND patients. In addition, oncological safety and perioperative complications of the unilateral template resection was compared to the full bilateral one. Design/Setting/Participants: Between 2003 and 2018, 504 RPLNDs have been performed in 434 patients. The database of consecutive patients was queried to identify 171 patients with PC-RPLND after 1st line chemotherapy for a non-seminoma with or without bilateral template resection. Re-Do's, late relapse, salvage patients, and thoraco-abdominal approaches were excluded. Indication for a template resection was a unilateral residual mass mainly <5 cm as published (1). Outcome, Measurement, and Statistical Analysis: Descriptive statistics were used to report preoperative features, postoperative outcomes and patterns of recurrence, on the overall population and after stratification for the type of resection (bilateral vs. unilateral). Kaplan-Meier analyses were used to describe recurrence- and cancer-specific mortality-free survival rates at different time points. Results and Limitations: Overall, 90 and 81 patients underwent unilateral and bilateral radical resection, respectively. Median size of residual mass was 7 cm for bilateral and 4 cm for unilateral template resection. Clinical stage II and III were present in 31 and 69% of patients, respectively. Median follow-up was 14.5 months (IQR 3.3–37.6). The 1- and 2-year recurrence-free survival rates were 91 and 91%, and 77 and 72% for patients treated with unilateral template and bilateral resection, respectively (p = 0.0078). Median time to recurrence was 9.5 and 9 months in template and bilateral resection group, respectively. Adjunctive procedures were performed in 56 patients (33%) and were significantly more frequent in the bilateral resection group (43 vs. 23%, p = 0.006). The overall high-grade complication rate (Clavien-Dindo ≥ III) was 6, 3, and 9% in unilateral template and bilateral resection group, respectively (p = 0.6). The rate of preservation of antegrade ejaculation was significantly higher in the unilateral group. Conclusions: Antegrade ejaculation in patients undergoing unilateral template resection with a residual mass <5 cm can be preserved at a much higher rate. Moreover, this surgical procedure is oncologically safe in terms of mid-term recurrence and CSM-free survival rates. This data undermines the growing evidence of limited PC-RPLND being justifiable in strictly unilateral residual mass <5 cm. This data has to be confirmed with a longer follow-up regarding in-field and retroperitoneal recurrences.